PENDEKATAN MAQASHID SYARIAH DALAM MENCEGAH PERCERAIAN DI ERA MEDIA SOSIAL - Muhammad Abyan Fariedza; Misbahuzzulam (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines the effectiveness of the Maqashid Syariah approach—hifzh al-din (religion), hifzh al-nafs (soul), hifzh al-‘aql (mind), hifzh al-mal (wealth), and hifzh al-nasl (progeny)—in preventing divorce in the social media era, using a descriptive qualitative approach based on literature review. The literature analysis includes Islamic premarital modules and Sharia mediation to strengthen family commitment; Sharia digital literacy and gadget-free zones to reduce virtual jealousy; online psychosocial counseling and Islamic support forums to reduce stress and psychological isolation; Sharia financial management training to mitigate consumerist pressure caused by flexing on social media; and digital da'wah programs, prayer reminder apps, and negative content filtering to enhance spiritual discipline and redirect focus away from harmful content. The research findings confirm that the integrated Maqaṣhid Sharia intervention significantly builds the foundation of religious values, sound reasoning, mental well-being, economic stability, and generational sustainability. Therefore, it is recommended that Religious Courts, da'wah institutions, and Islamic counseling practitioners integrate these five pillars into divorce prevention programs in the digital age.